How do humans and plants feel the heat?. (July 2022) - Guihur, Anthony; Rebeaud, Mathieu E.; Bourgine, Baptiste; Goloubinoff, Pierre
Abstract : The 2021 Nobel prize was awarded for the discovery of the animal thermosensory channel TRPV1. We highlight notable shared features with the higher plant thermosensory channel CNGC2/4. Both channels respond to temperature-induced changes in plasma membrane fluidity, leading to hyperphosphorylation of the HSF1 transcription factor via a specific heat-signaling cascade.